Analysis of the Effects of Paylater Activities on Millennials' Financial Performance in E-Commerce Companies (Case Study of Tokopedia) - Wijaya, M Khadri; Harahap, Lily Rahmawati; Aryanti, Rahmi (Journal of Management, Economic, and Accounting, 2025)
This study aims to analyze the effect of paylater activities on the financial performance of PT GoTo, especially for Gen Z in Palembang City. This research uses quantitative and qualitative approaches. Quantitative data obtained from the company's financial statements and historical data from many paylater users, analyzed using financial ratios and also using the VAR test. Qualitative data was obtained from a questionnaire distributed to 100 Gen Milenial respondents who were interested in investing in stocks. Statistical analysis using the VAR test was conducted to see if there was a difference between the two companies. The results showed that the effect of paylater activity had an effect on the financial performance of PT GoTo. The financial performance of the two companies did not show a significant difference in the profit ratio, solvalbility ratio, and activity ratio, but in the liquidity ratio showed a significant difference. Gen-Milenial Palembang city has a high interest in the use of paylater, most of them are not actively using it due to financial constraints and limited knowledge of using paylater.